Investigating and implementing an extensible, adaptable game plan for digital initiatives at a large state university. Issue 4 (1st August 2016) - Dressler, Virginia A.
Abstract : Purpose: The purpose of this paper is to explore the process of assessing the needs of a digital repository. The study's institution – Kent State University, a large state university – is currently re-envisioning their digital library services to accommodate emerging technologies with an agile framework and platform. This paper includes discussion on the process of creating a sustainable digital initiatives program, a plan of action for migration, platform decision rationale and an overview of planning for future projects that is both flexible and extensible in nature. Design/methodology/approach: The article's approach is to examine the process of review and selection of the digital repository at Kent State University through the needs and requirements checklist the team devised according to the institution's specifications. Literature published in the past five years is reviewed and applied to the selection process. The author maps out a plan that can be adaptable for growth and sustainability for a content management system. Findings: Using models identified in the article, the team mapped a solution that can enhance the use and interaction by patrons to digital collections as well as provide a method to ensure the longevity of digital assets. Originality/value: The article addresses issues that are inherent to digital content management systems of all shapes and sizes, and strives to provide a solution that would be relevant and applicable to many types of institutions in regard to digital repositories.